Blood Macro and Micro Mineral Status of Calves During Treatment for Industrial Fluorosis with Tamarind (Tamarindus indica) Fruit Pulp - Pati, M.; Parida, G. S.; Mandal, K. D.; Gupta, A. R.; Swain, R. K.; Senapati, S. K.; Patra, R. C. (Indian Journal of Animal Nutrition, 2018)
The present investigation was carried out to examine the mineral status in fluorotic calves reared around the vicinity of aluminium smelter plant during treatment with Tamarindus indica fruit pulp. Eighteen calves of 6-12 months age having average body wt of 81.2 kg were selected. Group T1 calves (n=6) from fluoride free areaserved as healthy controls. Twelve calves with typical dental lesion of fluorosis and high plasma F level were selected from the industrial fluorosis affected area (having toxic level of F in soil, water and fodder samples) and were divided in two equal groups consisting of 6 animals each. Group T2 animals received no treatment andserved as disease control and group T3 animals were given tamarind pulp powder (79.3% DM) @ 30 g/calf/day for a period of 60 days. Blood samples were collected from the animals of all the groups on day 0, 30 and 60 of the experiment for estimation of macro (Ca, P and Mg) and micro (Fe, Zn, Mn and Co) minerals. Significantly (P